Mechanistic insights into the antitumor effects of astragaloside IV and astragalus polysaccharide in digestive system cancers - Cui, Zhenhua; Shang, Qingxin (Frontiers in Pharmacology, 2025)
Malignant tumors of the digestive system are among the leading causes of cancer-related mortality worldwide. Characterized by complex pathogenesis and insidious early symptoms, these cancers remain major challenges in clinical management. With the growing interest in natural medicines, Astragalus membranaceus and its active components, Astragaloside IV (AS-IV) and Astragalus polysaccharide (APS), have attracted considerable attention for their therapeutic potential against digestive system malignancies. Based on more than 41 peer-reviewed studies published in recent years, this review summarizes the key antitumor mechanisms of AS-IV and APS in hepatocellular carcinoma, colorectal cancer, gastric cancer, and other digestive system malignancies. AS-IV exerts anticancer effects through the regulation of PI3K/AKT, MAPK, NF-κB, and TGF-β/Smad pathways, leading to apoptosis induction, inhibition of epithelial–mesenchymal transition, modulation of the tumor immune microenvironment, reversal of multidrug resistance, and enhancement of chemosensitivity. APS, a bioactive macromolecule with immunostimulatory and multitarget regulatory properties, enhances antitumor immunity by activating dendritic cells, promoting macrophage polarization, and suppressing immune evasion, while also improving the efficacy of chemotherapy and targeted therapies. This comprehensive review highlights molecular targets, signaling networks, and novel delivery strategies of AS-IV and APS, providing mechanistic insights and translational perspectives for their potential application in digestive system cancers.